Dynamic properties of the coupled Oregonator model with delay - Wu, Xiang; Zhang, Chunrui (Nonlinear Analysis: Modelling and Control, 2013)
This work explores a coupled Oregonator model. By analyzing the associated characteristic equation, linear stability is investigated and Hopf bifurcations are demonstrated, as well as the stability and direction of the Hopf bifurcation are determined by employing the normal form method and the center manifold reduction. We also discussed the Z2 equivariant property and the existence of multiple periodic solutions. Numerical simulations are presented to illustrate the results in Section 5.
Keywords: delay; Hopf bifurcation; stability; coupled Oregonator model